2019
DOI: 10.29261/pakvetj/2019.037
|View full text |Cite
|
Sign up to set email alerts
|

The Under Reported Issue of Antibiotic-Resistance in Food-Producing Animals in Pakistan

Abstract: The recent revelation of a plasmid-mediated colistin resistant superbug isolated in China from food-producing animals (FPAs) and epidemic of a pan-drug resistant human typhoid strain in Hyderabad, Pakistan proved the notion that novel mechanisms of antibiotic resistance will emerge as we continue to rely on consistent use of antibiotics. The emergence and dissemination of antibiotic resistance is accelerated up by indiscriminate and incessant usage of antibiotics due to uncontrolled infections in hospital sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 53 publications
5
34
1
Order By: Relevance
“…The prevalence of Salmonella in beef samples in our research study is higher as compared to previous research studies [33][34][35][36]. However, some research studies have reported more than 60% prevalence in beef samples [37][38][39][40]. The Salmonella prevalence in beef is much lower in developed countries like USA due to strict control measures.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The prevalence of Salmonella in beef samples in our research study is higher as compared to previous research studies [33][34][35][36]. However, some research studies have reported more than 60% prevalence in beef samples [37][38][39][40]. The Salmonella prevalence in beef is much lower in developed countries like USA due to strict control measures.…”
Section: Discussioncontrasting
confidence: 71%
“…Salmonella isolates of raw beef origin exhibited high resistance to antibiotics of therapeutic importance such as Tetracycline, Oxytetracycline, Ampicillin, Amoxicillin and Ciprofloxacin which reflects their high use in the livestock industry in Pakistan [39]. The overuse and misuse of antibiotics in livestock industry have greatly contributed to the spread of MDR bacteria especially Salmonella to humans via the food chain [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total consumption of antimicrobials by chickens in Asia is expected to increase by 129% between 2010 and 2030, driven in large part by increasing chicken consumption in India and Pakistan concomitant with population growth and poor antibiotic stewardship (Hussain et al, 2015;Van Boeckel et al, 2015). Although policies have recently been introduced to encourage restricted antibiotic use in food animals in Pakistan, challenges to regulation and surveillance remain such that accurate estimates of antibiotic usage in poultry rearing are elusive (Rahman and Mohsin, 2019). The types of antibiotics used might be inferred from the multi-drug resistance profiles identified in E. coli isolates by previous studies, alarmingly with high prevalence to antibiotics of clinical importance (Idrees et al, 2011;Akhtar et al, 2016;Azam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although NAP-AMR urged the monitoring and reduction in the level of AMU in animals, nationwide surveillance to monitor AMU in livestock has not been established yet ( 16 ). Therefore, this study is designed to quantify AMU on a convenience sample of two large corporate commercial dairy farms for 1 year to provide the first baseline study on AMU at the farm-level in Pakistan.…”
Section: Introductionmentioning
confidence: 99%